2016
DOI: 10.1159/000454677
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Parvalbumin-, Somatostatin-, and Cholecystokinin-Expressing Neurons in Rat Brain following Prenatal Immune Activation and Maternal Iron Deficiency

Abstract: Prenatal maternal infection and maternal iron deficiency during pregnancy are 2 early environmental insults associated with increased risk for schizophrenia in offspring. Substantial evidence suggests that abnormalities in inhibitory γ-aminobutyric acid (GABA) interneuron function, especially in the parvalbumin subtype of GABA interneuron, both developmentally and in adulthood, may contribute mechanistically to cognitive deficits and psychotic symptoms in schizophrenia. This study used a rat model to test whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Reductions in both regions, however, are contrary to our hypothesis that postulated that the cortex is more susceptible to MIA than the striatum. Given that our previous behavioural study showed working memory impairments in GD19 polyI:C offspring, but not GD10 polyI:C offspring 50 , and multiple studies show a central role of somatostatinergic signalling in cognitive function [76][77][78][79] , our present findings suggest that the combined SSTR2 mRNA deficits in cortex and striatum (found only at GD19), in combination with the SST mRNA deficits in cortex and striatum, may contribute to the working memory deficits apparent in late gestation MIA offspring.…”
Section: Discussionsupporting
confidence: 51%
“…Reductions in both regions, however, are contrary to our hypothesis that postulated that the cortex is more susceptible to MIA than the striatum. Given that our previous behavioural study showed working memory impairments in GD19 polyI:C offspring, but not GD10 polyI:C offspring 50 , and multiple studies show a central role of somatostatinergic signalling in cognitive function [76][77][78][79] , our present findings suggest that the combined SSTR2 mRNA deficits in cortex and striatum (found only at GD19), in combination with the SST mRNA deficits in cortex and striatum, may contribute to the working memory deficits apparent in late gestation MIA offspring.…”
Section: Discussionsupporting
confidence: 51%
“…Overall, the changes in PV interneurons bear high resemblance to the observations in established animal models of maternal inflammation [ 26 , 27 , 29 ]. As previously discussed, we were unable to detect maternal inflammation 11 and 28–29 days after exposure, but we cannot rule out that inflammation was present at earlier time points.…”
Section: Discussionmentioning
confidence: 55%
“…This is in contrast to a recent observation that reported an increase in the number of PV immunoreactive cells in the dlPFC of adolescent male rats from LPS-treated dams (50 mg/kg i.p. on GD15/16) (Boksa et al, 2017). Other neuronal deficiencies, including in dopaminergic and serotonergic neurons, have been described in MIA models (Meyer et al, 2009b;Boksa, 2010;Vuillermot et al, 2012;Pratt et al, 2013;Smith et al, 2014;Squarzoni et al, 2014;Depino, 2015;Reisinger et al, 2015).…”
Section: Developmental Dynamicsmentioning
confidence: 96%
“…In contrast, MIA induction in mid-gestation (GD13-15) with Poly(I:C) results in an increase in Purkinje cell numbers in juvenile and adult mice (Aavani et al, 2015). on GD15/16) (Boksa et al, 2017). Defects in the development and function of interneurons have been implicated in a number of psychiatric disorders (Mar ın, 2012).…”
Section: Effect Of Mia On Neurogenesis and Neuronal Developmentmentioning
confidence: 99%